Śāḵīr. К вопросу о наемном труде на древнем Ближнем Востоке (1-я половина I тысячелетия до н. э.) - Амусин, И. Д.
Amusin, I. D., Śākhîr. On the Problem of Hired Labour in the Ancient Near East (1-st Half of the 1-st Millennium В. C.); engl. Résumé S. 267f.